A matter of degrees: A systematic review of the ergogenic effect of pre-cooling in highly trained athletes - Rodriguez, M. A.; Piedra, J. V.; Sánchez-Fernández, M.; del Valle, M.; Crespo, I.; Olmedillas, H. (International Journal of Environmental Research and Public Health, 2020)
The current systematic review evaluated the effects of different pre-cooling techniques on sports performance in highly-trained athletes under high temperature conditions. PubMed/MEDLINE, EMBASE, Web of Science, CENTRAL, Scopus, and SPORTDiscus databases were searched from inception to December 2019. Studies performing pre-cooling interventions in non-acclimatized highly-trained athletes (>55 mL/kg/min of maximal oxygen consumption) under heat conditions (=30 °C) were included. The searched reported 26 articles. Pre-cooling techniques can be external (exposure to ice water, cold packs, or cooling clothes), internal (intake of cold water or ice), or mixed. Cooling prior to exercise concluded increases in distance covered (1.5-13.1%), mean power output (0.9-6.9%), time to exhaustion (19-31.9%), work (0.1-8.5%), and mean peak torque (10.4-22.6%), as well as reductions in completion time (0.6-6.5%). Mixed strategies followed by cold water immersion seem to be the most effective techniques, being directly related with the duration of cooling and showing the major effects in prolonged exercise protocols. The present review showed that pre-cooling methods are an effective strategy to increase sports performance in hot environments. This improvement is associated with the body surface exposed and its sensibility, as well as the time of application, obtaining the best results in prolonged physical exercise protocols.